2000
DOI: 10.1038/labinvest.3780050
|View full text |Cite
|
Sign up to set email alerts
|

Release and Complex Formation of Soluble VEGFR-1 from Endothelial Cells and Biological Fluids

Abstract: SUMMARY:One of the key molecules promoting angiogenesis is the endothelial cell-specific mitogen, vascular endothelial growth factor (VEGF or VEGF-A), which acts through two high-affinity receptor tyrosine kinases (VEGFR), VEGFR-1 (or Flt-1) and VEGFR-2 (or KDR/Flk-1). It was shown before that a soluble variant of VEGFR-1 (sVEGFR-1) can be generated by differential splicing of the flt-1 mRNA. This soluble receptor is an antagonist to VEGF action, reducing the level of free, active VEGF-A, and therefore, plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
135
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(155 citation statements)
references
References 35 publications
14
135
0
6
Order By: Relevance
“…Similar complexes of 220 kD have been reported in human umbilical vein endothelial cells (12). Furthermore, Hornig et al (31) reported that only 5-10% of the soluble receptor is detected as uncomplexed receptor protein. In pulmonary artery cytosolic fraction, three bands were identified for VEGFR1.…”
supporting
confidence: 50%
“…Similar complexes of 220 kD have been reported in human umbilical vein endothelial cells (12). Furthermore, Hornig et al (31) reported that only 5-10% of the soluble receptor is detected as uncomplexed receptor protein. In pulmonary artery cytosolic fraction, three bands were identified for VEGFR1.…”
supporting
confidence: 50%
“…free VEGF and free PlGF (22,23). We first confirmed that these ELISA kits measured only unbound VEGF or PlGF by performing a standard curve for VEGF and PlGF proteins in the presence of exogenous recombinant sFlt1.…”
Section: Figurementioning
confidence: 56%
“…23 Moreover, increased sFlt-1 is suggested to bind to these angiogenic factors and decrease their free fractions. 18,24 Additionally, sFlt-1 competes with VEGFR-2 for VEGF, leading to disturbed angiogenesis, endothelial dysfunction, glomerular damage, impaired glomerular repair and increased apoptosis. 17,25 These changes contribute to the development of hypertension and proteinuria in PE.…”
Section: Discussionmentioning
confidence: 99%